Coronary endothelial function testing provides superior discrimination compared with standard clinical risk scoring in prediction of cardiovascular events. Issue 3 (May 2016) - Reriani, Martin; Sara, Jaskanwal D.; Flammer, Andreas J.; Gulati, Rajiv; Li, Jing; Rihal, Charanjit; Lennon, Ryan; Lerman, Lilach O.; Lerman, Amir
Abstract : Background: Endothelial dysfunction is regarded as the early stage of atherosclerosis and is associated with cardiovascular (CV) events. This study was designed to determine whether assessment of coronary endothelial function (CEF) is safe and can reclassify risk in patients with early coronary artery disease beyond the Framingham risk score (FRS). Methods and results: CEF was evaluated using intracoronary acetylcholine in 470 patients who presented with chest pain and nonobstructive coronary artery disease. CV events were assessed after a median follow-up of 9.7 years. The association between CEF and CV events was examined, and the net reclassification improvement index (NRI) was used to compare the incremental contribution of CEF when added to FRS. The mean age was 53 years, and 68% of the patients were women with a median FRS of 8. Complications (coronary dissection) occurred in three (0.6%) and CV events in 61 (13%) patients. In univariate analysis, microvascular CEF [hazard ratio (HR) 0.85, 95% confidence interval (CI) 0.72–0.97, P =0.032] and epicardial CEF (HR 0.73, 95% CI 0.59–0.90, P =0.01) were found to be significant predictors of CV events, whereas FRS was not (HR 1.05, 95% CI 0.85–1.26, P =0.61). When added to FRS, microvascular CEF correctly reclassified 11.3% of patients [NRI 0.11 (95% CI 0.019–0.21)], epicardial CEF correctly reclassified 12.1% of patients [NRI 0.12 (95% CI −0.02 to 0.26)], and the combined microvascular and epicardial CEF correctly reclassified 22.8% of patients [NRI 0.23 (95% CI 0.08–0.37)]. Conclusion: CEF testing is safe and adds value to the FRS, with superior discrimination and risk stratification compared with FRS alone in patients presenting with chest pain or suspected ischemia.